Modeling Plastics Exposure for the Marine Biota: Risk Maps for Fin Whales in the Pelagos Sanctuary (North-Western Mediterranean) - Guerrini, Federica; Mari, Lorenzo; Casagrandi, Renato (Frontiers in Marine Science, 2019)
The Mediterranean basin is among the most impacted marine ecoregions globally, being at the same time semi-enclosed by densely populated countries and crossed by trafficked maritime routes. Such anthropogenic pressure threatens both the quality of its waters and the high biodiversity living in them, making the role of Marine Protected Areas (MPAs) crucial for preserving species suitable habitats. Under the European Union Marine Strategy Framework Directive, marine litter has been recognized as one of the principal causes of marine pollution, and public awareness on its environmental and biological impacts is raising. Using a quantitative and data-driven modelling approach, here we assess the presence of plastic waste within the feeding grounds of the fin whale Balaenoptera physalus, an endangered cetacean for which there is increasing evidence of impacts due to microplastic ingestion. To this end, we analyze a decade (2000 - 2010) of advection patterns of marine plastic litter, modelled with a Lagrangian approach. Particles are released in the MPA Pelagos, the International Sanctuary for the Protection of Mediterranean Marine Mammals (North-Western Mediterranean, between France, Italy and Monaco), from different sources (i.e., untreated waste along coasts, plastic discharged from rivers and plastic pollution released along maritime shipping routes). Risk of exposure of fin whales to microplastic pollution is evaluated by interlacing plastic litter distribution maps obtained through modelling with maps of suitable habitats obtained from the elaboration of satellite chlorophyll-a data in species-specific visited areas. Our modelling results show that all the three main sources of plastic litter taken into account clearly contribute to impacting cetaceans in the Sanctuary, yet in a different manner. The procedure formalized here can be extended to assess the risk caused by plastic pollution in other MPAs as well as to evaluate possible impacts on other taxa, thus informing targeted actions to tackle the complex issue of marine litter.